UJI AKTIVITAS ANTIINFLAMASI KOMBINASI EKSTRAK DAUN SALAM (Syzygium polyanthum (Wight) Walp) dan EKSTRAK DAUN PEPAYA (Carica papaya L.) TERHADAP UDEMA KAKI TIKUS PUTIH JANTAN YANG DIINDUKSI KARAGENIN - Syahputra, Dhika Adhil; Samodra, Galih; Prabandari, Rani (Jurnal Farmasi & Sains Indonesia, 2022)
Inflammation or inflammation is the body's normal response to tissue damage caused by physical trauma, chemical and microbial damage. Plants that are thought to have anti-inflammatory properties are bay leaves (Syzygium polyanthum (Wight) Walp). Which acts as an anti-inflammatory in bay leaves and papaya leaves are flavonoids. Bay leaf and papaya leaf extracts were extracted using 70% ethanol by maceration method. The test animals were divided into 7 groups, namely a negative control group (Na CMC), a positive group (Diclofenac Sodium 50 mg), a single dose group of 100 mg/kgBW bay leaf extract, a single dose group of 100 mg/kgBW papaya leaf extract, and a combination group of leaf extracts. salam and papaya leaf extract 50mg/kgBB: 50mg/kgBB, 150mg/kgBB: 100mg/kgBB, 250mg/kgBB: 200mg/kgBB. Treatment 1 hour after the hind legs of rats was induced by subplantar carrageenin. The results showed that the combination of bay leaf and papaya leaf extracts had anti-inflammatory activity. The results of the calculation of the inflammatory power in the combination group showed inflammatory activity.